HUBUNGAN RIWAYAT PAPARAN PESTISIDA DENGAN JUMLAH ERITROSIT, MCV, MCH, DAN MCHC PADA PETANI SAYURAN DI DESA SUMBEREJO KECAMATAN NGABLAK KABUPATEN MAGELANG - Ilya Farokha Rizqiyana; Onny Setiani; Hanan Lanang Dangiran (Jurnal Kesehatan Masyarakat (Undip), 2017)
Farmers antisipate pest of plants early by increasing the amount of pesticide, the frequency of spraying pest and the composition of pesticide used. The use of pesticides with high doses and continuously will cause some losses, for examples accumulating residue of pesticide in agricultural products, polluting the agricultural environment, decreasing the productivity, poisoning animals, poisoning humans that give bad affects for health. The purpose of this research is to find outthe relation between the exposure of pesticide and the quantities of eritrocite, MCV, MCH, and MCHC to vegetable farmer in Sumberejo Ngablak Magelang. This research is a quantitative research with cross sectional approach. This research observes 110 respondents. The sample uses purposive sampling technique. The instrument used in this research is questionnaires and hematology analyzer. The data were analyzed by univariate, bivariate using chi-square test with 95% significance level, and spearman test.The average age of the respondents were 43 years old. Moreover, the formal education of the respondents were dominated by primary school graduate which is 58.1%. The results showed that there was a negative relationship between blood cholinesterase and erythrocytes (p = 0.046, r = -0.306). However, there was no correlation between cholinesterase level with MCV, MCH on vegetable farmers in agricultural area in Sumberejo Village Ngablak Magelang District, with p = 0,976, r = 0,004 for MCV, p = 0,880, r = - 0,024 for MCH. Whereas, the variable exposure of pesticide, the duration of work, the number of active ingredients of pesticide and the use of APD had no relation with the amount of erythrocytes, MCV, MCH (p> 0,05). Farmers are expected to apply pesticides properly, precisely and safely. Therefore, it will not pollute the environment and spraying farmers and the community is avoided from exposure to pesticides.